Requirements for computational rule checking of requests for proposals (RFPs) for building designs in South Korea. Issue 3 (August 2015) - Uhm, Miyoung; Lee, Ghang; Park, Younghyn; Kim, Sanghun; Jung, Jiwon; Lee, Jin-kook
Highlights We analyze objects and methods required for checking automated design compliance. We analyze 27 RFPs for various types of large public buildings in South Korea. Only 14% of over 9800 RFP sentences are analyzed as being computer-interpretable. Three types of objects and 29 types of methods are derived. The sufficiency of the objects and methods is validated using additional RFPs.